Business Model Canvas : Intelligent Windows / Noor Alia Yamin - Yamin, Noor Alia (2020)
Intelligent Windows provide windows grilles and glass with great efficiency, safety and security. For example, window grilles can be opened in a short time with aided of technology fingerprint scanner which occupants can use during emergency like fire. The transparency of window glass also can be changed from transparent to opaque or vice versa which they comfort and feel safe when staying at home without worrying people outside can see inside the home through windows